CRISPR-Cas13a Based Visual Detection Assays for Feline Calicivirus Circulating in Southwest China - Huang, Jian; Liu, Yunjia; He, Yuwei; Yang, Xiaonong; Li, Yan (Frontiers in Veterinary Science, 2022)
Feline calicivirus (FCV) is a well-known causative pathogen for upper respiratory infection in cats, and its highly genomic variability challenges the existing molecular diagnositc methods in clinical settings. Thus, we developed two rapid, sensitive and visual assays for FCV nucleic acids detection based on RPA reaction and CRISPR-Cas13a system (FCV-Cas13a assays) and validate their efficiency by comparing with the reference real-time quantitative PCR (RT-qPCR) method. cDNAs, dual crRNAs, optimal RPA primers were prepared respectively targeting FCV ORF1 gene. In addtion, purified LwCas13a protein was obtained. In order to confirm the validity of FCV-Cas13a, seven reaction systems (RSs) with differernt components were tested, and visual readouts were displayed by lateral flow dipstick (FCV-Cas13a-LFD) and fluoresence detector (FCV-Cas13a-FLUOR). Then, sensitivity tests, specificity tests and clinical verification were carried out. The results showed that the established FCV-Cas13a assays were capable of detecting FCV nucleic acids in presetting reaction system without cross-reactivity with other feline associated pathogens, and the detection limit was as low as 5.5 copies/μl for both visual methods. Besides, the positive rate of FCV-Cas13a in 56 clinical samples (67.9 %, 38/56) was notably higher than that of RT-qPCR (44.6%, 25/56) (p<0.001), including additional 13 presumptive samples. In conclusion, FCV-Cas13a assasys provided a reliable and visual diagnostic approach for FCV field detection.